The Influence of Ka‘b al-Ahbar on Islamic Political Thought from 15 AH/637 AD until 34 AH/655 AD - Jaradat, Mohammad Faris; Qobbaj, Amer Ahmad (Jordan Journal for History and Archaeology, 2025)
The influence of Ka‘b al-Ahbar (d. 34 AH/655 AD) began to appear in Islamic political thought after he settled in ash-Shām, through the circulation of his Jewish mythological narratives. Some of them had an echo in political thought, especially when Ka‘b made the sultan the shadow of God on earth, although they appeared in a doctrinal character, given Ka‘b’s personality before his conversion to Islam as a Jewish cleric, working as a special advisor to the governor. The warnings of Caliph Omar bin Al-Khattab (13-23 AH/635-645 AD) had limited his impetus, which prevented him from further identifying with his Jewish culture. However, during the reign of Caliph Othman bin Affan (23-35 AH/645-656 AD), he succeeded in establishing relationships, some of which had a political nature. This aroused the resentment of some of the senior Companions, which forced Kaab to migrate to ash-Shām, where he became active in spreading his Jewish narratives, which carried a political connotation, related to the political system as an absolute monarchy. He left an intellectual imprint that contributed to the crystallization of the political line that characterized Umayyad rule (41-132 AH/662-750 AD), where the influence of his narratives on Islamic political intellectual theory was evident among many scholars and thinkers who adopted this theory and worked to establish it, indirectly, in the context of the deterministic political doctrine, which called for voluntary submission to the sultan, the holder of power and tribal loyalty.